Spectral properties of smart LED lamps - Kusznier, Jacek; Wojtkowski, Wojciech (Photonics Letters of Poland, 2020)
Intelligent LED lamps are most often used in intelligent lighting installations. They frequently use one of two different ways to obtain white light. The first is the mixing of monochrome lights R, G and B. The second way is to mix the light of the blue diode with the yellow phosphor radiation. Adjusting the luminous flux in RGBW LED lamps causes greater changes in the position of the chromaticity point than in the case of CW WW LED lamps. In the case of big changes, this can lead to a visible change in the perceived color. Full Text: PDF References: https://re.jrc.ec.europa.eu/pvg_tools/en/tools.html [DirectLink] https://dateandtime.info/pl [DirectLink] J. Kusznier and W. Wojtkowski, "Impact of climatic conditions on PV panels operation in a photovoltaic power plant," IEEE, 2019 15th Selected Issues of Electrical Engineering and Electronics (WZEE), Zakopane, Poland, 2019, pp. 1-6 [CrossRef] J. Kusznier and W. Wojtkowski, "Impact of climatic conditions and solar exposure on the aging of PV panels," IEEE, 2019 15th Selected Issues of Electrical Engineering and Electronics (WZEE), Zakopane, Poland, 2019, pp. 1-6 [CrossRef] https://www.weatheronline.pl/weather/ [CrossRef] L.T. Sharpe, A. Jagla, W. Jägle, "A luminous efficiency function, V*(λ), for daylight adaptation", J. Vision 5(11), 948 (2012) [CrossRef] http://www.ee.co.za/article/integrating-sphere-data-sincere.html [DirectLink] Simunovic M. P., "On Seeing Yellow The Case for, and Against, Short-Wavelength Light-Absorbing Intraocular Lenses", Archives of Ophthalmology, vol. 130, no. 7, pp. 919-926, 2012 [CrossRef] I. Fryc, "Important parameters of multichannel spectroradiometer", Przeglad Elektrotechniczny R. 88(4a), pp. 230-231 (2012) [DirectLink] I. Fryc, "Measurement techniques of optical LEDs properties performed with compliance conformity with CIE 127:2007 standard", Przeglad Elektrotechniczny R. 85(11), pp. 317-319 (2009) [CrossRef] J. Kowalska, I. Fryc, "Colour rendition quality of typical fluorescent lamps determined by CIE Colour Fidelity Index and Colour Rendering Index", Przeglad Elektrotechniczny R. 95(7), pp. 94-97 (2019) [CrossRef] M. Gilewski, L. Gryko, A. Zajac, "Digital controlling system to the set of high power LEDs", Proc. of SPIE, 8902, 89021D, 2013 [CrossRef] M. Gilewski, "The ecological hazard of artificial lighting in greenhouses" Photonics Letters of Poland, vol. 11 Issue: 3 Pages: 87-89, 2019 [CrossRef] I. Fryc and T. Dimitrova-Grekow, "An automated system for evaluation of the quality of light sources," 2016 IEEE Lighting Conference of the Visegrad Countries (Lumen V4), Karpacz, 2016, pp. 1-4. [CrossRef] I. Fryc, "The spectral power distribution of LED driven by square shape pulses", Przeglad Elektrotechniczny R. 88(6), pp. 131-133 (2012) [DirectLink] I. Fryc, "LED’s spectral power distribution under different condition of operating temperature and driving current", Przeglad Elektrotechniczny R. 86(10), pp. 187-189 (2010) [DirectLink] J. Kusznier, "Changes in the Spectral Power Distribution of Light Sources for Smart Lighting," IEEE, 2018 14th Selected Issues of Electrical Engineering and Electronics (WZEE), Szczecin, Poland, 2018, pp. 1-5 [CrossRef]